Trance in traditional Polish rural dance culture - Welcz, Henryk (Current Problems of Psychiatry, 2011)
Trance is a medical term contained in Chapter V of International Statistical Classification of Diseases and Related Health Problems (ICD-10) in the part of dissociational disorders (F44.3 together with possession) and means a disorder characterised by transitional loss of own identity and decline of complete understanding of the surroundings. In this article I would like to deal only with a part of the phenomena of trance, dependent on will, performed in traditional Polish rural dance culture. Phenomena of trances and ecstasy, which are frequently identified with each other, have been named by the researchers of the subject as altered states of conscience and mean particular states caused by physiological or psychological factors, which are characterised by the deviation in subjective understanding of the reality and the change towards the approved forms of behaviour during experiencing them. Musical-dancing trance rituals are perceived as the elements of the phenomenon of Catharsis. Polish traditional dances like mazurek or oberek include trance elements similar to tarantella, whirling dervishes and Hasidic dances. Impressions which appear during the performance of dances with rotation are not as deep as trances described as states of conscience with deviation in subjective understanding of the reality and the change towards the approved forms of behaviour during experiencing them. Long-time rotation and changes in labyrinthine system of brain are very important.